The terrorist album: apartheid's insurgents, collaborators, and the security police - Dlamini, Jacob (Harvard University Press, 2020)
From racial types to terrorist types -- Apartheid's mismeasure -- The uncertain curator -- Perusals -- The petty state -- The embarrassed state -- Comrade Rashid -- The family bible -- The dompas -- Capitol drama -- Sins of history.